PUBLIC POLICY IN ISLAMIC FRAMEWORK: EXPLORING PARADIGM BASED ON ISLAMIC EPISTEMOLOGY - Abdulkader Cassim Mahomedya (Share: Jurnal Ekonomi dan Keuangan Islam, 2015)
Despite the concerted efforts of recent Islamic scholarship to establish a distinct identity for Islamic economics, they have enjoyed little success in doing so. One of the most important reasons for this vision of Islamic sciences remaining unfulfilled is that scant attention has been paid to the critical role of epistemology in the founding of an academic discipline. Consequently, and not unlike the other areas of Islamic social science, Islamic Economics has remained embedded within the epistemological-ontological foundations of Occidentalism, thereby enslaving itself to the mainstream theories and tools of neoclassical microeconomics and Keynesian macroeconomics. This has been the central debility facing Islamic economists in establishing a distinct identity for their field of inquiry. This paper aims to highlight the importance of the relationship between epistemology, science, and Islamic economics. Only after this nexus is understood and appreciated, will it meaningful to articulate an episteme for Islamic economics, and to derive therefrom and construct thereupon a matrix of concepts, ontological categories and axioms opposite to that episteme. This is critical if Islamic economists and Muslim social scientists aspire to realise the objectives of Islam and avoid the pitfalls of their counterparts in the western world. They have to chart a new and fresh way forward for their science, consistent with a worldview based on Islam's authentic sources. =========================================== Meskipun upaya-upaya terpadu pengetahuan Islami terkini untuk membangun suatu identitas yang berbeda bagi ilmu ekonomi Islam, ada sedikit keberhasilan dari upaya- upaya tersebut. Salah satu alasan yang paling penting untuk visi ilmu pengetahuan Islami yang masih belum diisi adalah minimnya perhatian yang ditujukan kepada peranan kritis epistemology dalam membentuk suatu disiplin akademik. Oleh karena itu, tidak seperti area-area lain dalam ilmu sosial Islami, Ekonomi Islam telah dan masih menyertakan dasar-dasar epistemology-ontology kebiasaan orang-orang barat (occidentalisme), sehingga masih terikat pada teori- teori arus utama dan perangkat ekonomi mikro neo-klasik dan ekonomi makro Keynesian. Hal ini menjadi kelemahan utama yang dihadapi oleh para ekonom Islam dalam membentuk suatu identitas yang berbeda dalam bidang penelitiannya. Kajian ini bertujuan untuk menekankan pentingnya hubungan antara epistemologi, ilmu pengetahuan, dan ekonomi Islam. Setelah keterkaitan ini dipahami dan disadari, hal ini akan memberi arti dalam mengartikulasikan suatu episteme bagi ekonomi Islam dan untuk memperoleh darinya dan kemudian mengkonstruksikan sebuah matrix konsep, kategori ontology dan aksioma yang tepat bagi episteme tersebut. Hal ini sangat mendesak jika para ekonom Islam dan para ahli ilmu sosial muslim bercita-cita untuk mewujudkan tujuan- tujuan Islam dan menghindari jebakan rekan- rekannya di dunia barat. Mereka harus merencanakan sebuah cara baru dan berbeda dalam memajukan ilmu pengetahuannya, konsisten dengan pandangan yang berdasarkan sumber-sumber Islam yang asli.